Is palindromic rheumatism amongst children a benign disease? - Yonatan Butbul-Aviel; Yosef Uziel; Nofar Hezkelo; Riva Brik; Gil Amarilyo (BMC, 2018)
Abstract Background Palindromic rheumatism is an idiopathic, periodic arthritis characterized by multiple, transient, recurring episodes. Palindromic rheumatism is well-characterized in adults, but has never been reported in pediatric populations. The aim of this study was to characterize the clinical features and outcomes of a series of pediatric patients with palindromic rheumatism. Methods We defined clinical criteria for palindromic rheumatism and reviewed all clinical visits in three Pediatric Rheumatology centers in Israel from 2006through 2015, to identify patients with the disease. We collected retrospective clinical and laboratory data on patients who fulfilled the criteria, and reviewed their medical records in order to determine the proportion of patients who had developed juvenile idiopathic arthritis. Results Overall, 10 patients were identified. Their mean age at diagnosis was 8.3 ± 4.5 years and the average follow-up was 3.8 ± 2.7 years. The mean duration of attacks was 12.2 ± 8.4 days. The most frequently involved joints were knees. Patients tested positive for rheumatoid factor in 20% of cases. One patient developed polyarticular juvenile idiopathic arthritis after three years of follow-up, six patients (60%) continued to have attacks at their last follow-up and only three children (30%) achieved long-term remission. Conclusions Progression to juvenile idiopathic arthritis is rare amongst children with palindromic rheumatism and most patients continued to have attacks at their last follow-up. Longer follow-up periods are required to predict the long-term outcomes of pediatric patients with palindromic rheumatism.